Measurement of the dipion mass spectrum in decays. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We measure the dipion mass spectrum in X(3872)--> J/psipi(+) pi(-) decays using 360 pb(-1) of pp collisions at square root s= 1.96 TeV collected with the CDF II detector. The spectrum is fit with predictions for odd C-parity ((3)S(1), (1)P(1), and (3)D(J)) charmonia decaying to J/psipi(+) pi(-), as well as even C-parity states in which the pions are from rho(0) decay. The latter case also encompasses exotic interpretations, such as a D(0)D(*0) molecule. Only the (3)S(1) and J/psirho hypotheses are compatible with our data. Since (3)S(1) is untenable on other grounds, decay via J/psirho is favored, which implies C= +1 for the X(3872). Models for J/psi - rho different angular momenta L are considered. Flexibility in the models, especially the introduction of rho - omega interference, enables good descriptions of our data for both L = 0 and 1.